CENTRAL INDUCTION POLICY (CIP) FOR THE POST GRADUATE RESIDENCY - Tahir Bashir Malik (Journal of University Medical & Dental College, 2019)
Central Induction Policy (CIP) for the post graduate residency programs in various disciplines has stirred the medical graduates across the province. The uprising number of fresh medical graduates from public and private medical colleges , and mounting interest of the doctors in post graduation have created a constraint on training slots especially the paid seats.